Mycoplasma synoviae LP78 is a fibronectin/plasminogen binding protein, putative adhesion, and potential diagnostic antigen - Han, Shuizhong; Wang, Ying; Wang, Lizhen; Chang, Wenchi; Wen, Bo; Fang, Junyang; Hou, Xiaolan; Qi, Xuefeng; Wang, Jingyu (Frontiers in Microbiology, 2024)
Mycoplasma synoviae (M. synoviae) is one of the major poultry pathogens causing infectious synovitis, airsacculitis, a high incidence of shell breakage, and egg production loss. However, the pathogenesis of M. synoviae remains unclear. Adhesion of mycoplasmas to host cells is a crucial step in infection and colonization. The purpose of this study was to determine the adhesive function of a putative P80 family lipoprotein (LP78) and evaluate its application in the detection of antibodies against M. synoviae. Recombinant LP78 (rLP78) was expressed in the supernatant component of Escherichia coli and mouse anti-rLP78 serum was prepared. Bioinformatic analysis and western blotting results revealed that LP78 was conservative among M. synoviae strains. It was distributed not only in the cytoplasm but also on the membrane of M. synoviae through western blotting and indirect immunofluorescence (IFA). The adherence of M. synoviae to DF-1 cells was significantly inhibited by mouse anti-rLP78 serum (p < 0.01). IFA revealed that rLP78 adhered to DF-1 cells, and this adherence was prevented by mouse anti-rLP78 serum. Furthermore, rLP78 was found to bind to the DF-1 cells membrane proteins in a dose-dependent manner by enzyme-linked immunosorbent assay (ELISA). Screening of DF-1 cells membrane proteins by western blotting showed that proteins with molecular weight of 35-40 kDa and 55-70 kDa bound to rLP78. Moreover, rLP78 was identified to be a fibronectin/plasminogen binding protein. The sensitivity and specificity of rLP78-based iELISA were 85.7% and 94.1%, respectively. The maximum dilution of positive serum (HI titer, 1:128) detected via rLP78-based iELISA was 1:6,400, whereas that detected using a commercial ELISA kit was 1:12,800-1:25,600. Both rLP78-based iELISA and the commercial ELISA kit detected seroconversion after 7 days of challenge and immunization. No cross-reactivity with positive sera against other avian pathogens was observed in rLP78-based iELISA. Collectively, these results indicate that LP78 is a fibronecti/plasminogen-binding adhesion protein of M. synoviae and a potential diagnostic antigen. The present study will facilitate a better understanding of the pathogenesis of M. synoviae and the development of new diagnostic.